Correction: Kim et al. Novel Gene Polymorphisms for Stable Warfarin Dose in a Korean Population: Genome-Wide Association Study. Biomedicines 2023, 11, 2308 - Jung Sun Kim; Sak Lee; Jeong Yee; Kyemyung Park; Eun Jeong Jang; Byung Chul Chang; Hye Sun Gwak (Biomedicines)
There was an error in the original publication [...]